A New Species of the Bug Genus Cicadula Zetterstedt, 1838 from Turkey: (Hemiptera: Cicadomorpha: Cicadellidae) - Zeybekoǧlu, Ü. (Max Kasparek Verlag, 2010)
A new species of Cicadula, Cicadula kartali sp. n., is described from Turkey. It is distinguished from the closest species, Cicadula quadrinotata (Fabricus, 1974), by the presence of a pair of lateral spines in the middle of the aedeagal shaft. © 2010 Taylor & Francis Group, LLC.
Keywords: Cicadellidae; Cicadula; New Species; Turkey